SnS2 Nanosheets/H‐TiO2 Nanotube Arrays as a Type II Heterojunctioned Photoanode for Photoelectrochemical Water Splitting. Issue 5 (4th February 2019) - Lin, Jianfei; Liu, Yong; Liu, Yongping; Huang, Chen; Liu, Wenhui; Mi, Xihong; Fan, Dayong; Fan, Fengtao; Lu, Huidan; Chen, Xiaobo
Abstract: Improving the separation efficiency of photogenerated electron–hole pairs and the conductivity of electrons to photoanode substrates are critical to achieve high‐performance photoelectrochemical (PEC) water splitting. Here, a SnS2 /H‐TiO2 /Ti heterojunction photoanode was fabricated with SnS2 nanosheets vertically grown on hydrogen‐treated TiO2 (H‐TiO2 ) nanotube arrays on a Ti substrate. It showed a significantly enhanced photocurrent of 4.0 mA cm −2 at 1.4 V (vs. reversible hydrogen electrode) under AM 1.5 G illumination, 70 times higher than that of SnS2 /TiO2 /Ti. Kelvin probe force microscopy measurements indicated that photogenerated electrons could be easily transported through the SnS2 /H‐TiO2 interface but not through the SnS2 /TiO2 interface. Through hydrogen treatment, defects were created in H‐TiO2 nanotubes to convert type I junctions to type II with SnS2 nanosheets. As a result, a high efficiency of electron–hole separation at the SnS2 /H‐TiO2 interface and a high electron conductivity in H‐TiO2 nanotubes were achieved and improved PEC performance. These findings show an effective route towards high‐performance photoelectrodes for water splitting. Abstract : Exactly your type : A type II heterojunctioned photoanode based on SnS2 nanosheets/hydrogenated TiO2 nanotube arrays (SnS2 /H‐TiO2 /Ti) shows a significantly enhanced photocurrent of 4.0 mA cm −2 at 1.4 V (vs. RHE), 70 times higher than a type I heterojunctioned photoanode of SnS2 nanosheets/TiO2 nanotube arrays (SnS2 /TiO2 /Ti). Hydrogenation creates defects in TiO2 nanotubes, improves their electrical conductivity and converts their junctions with SnS2 nanosheets from type I to type II.